Implementasi Strategi Pembelajaran Jigsaw dalam Pembelajaran Fikih di MTsN 4 Langkat - Milfa Yetty; Asmayani Asmayani; Ahmad Khairuddin (MAN 4 Kota Pekanbaru, 2025)
This study aims to describe the implementation of the Jigsaw learning strategy in Fiqh instruction at MTsN 4 Langkat, explain its implementation stages, and identify the supporting and inhibiting factors. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the principal, Fiqh teacher, and students. The findings reveal that the implementation of the Jigsaw strategy consists of three main stages: planning, implementation, and evaluation. The learning process is conducted through the formation of home groups and expert groups, enabling students to exchange knowledge collaboratively and take responsibility for mastering the assigned learning materials. Supporting factors include students’ readiness and the availability of learning resources, while inhibiting factors comprise limited learning motivation, insufficient cooperative learning skills, limited instructional time, and inadequate learning media. Overall, the findings indicate that the Jigsaw strategy promotes active, collaborative, and student-centered learning in Fiqh instruction.